The symbolic meaning in the lyrics of the song "Tutur Batin" by Yura Yunita - Annisa Salsabila Damayanti; Aulia Afniar Rahmawati (DIGICOM : Jurnal Komunikasi dan Media, 2023)
Semiotic Analysis of Self-Confidence Communication in the Lyrics of "Tutur Batin" by Yura Yunita using Charles Sanders Pierce's triadic approach to identify the meaning of self-confidence in the lyrics. This study aims to elucidate how the meaning of self-confidence is conveyed in the song lyrics based on Pierce's first, second, and third trichotomies. The analysis results indicate that the song "Tutur Batin" conveys messages about the importance of moral values, self-acceptance, and the freedom to be oneself. Semiotic analysis in this research provides a profound understanding of the meaning of self-confidence in the song lyrics and its relevance to the social context.